(untitled) (Latakia University Journal -Biological Sciences Series, 2019)
تم إجراء هذا البحث من بداية شهر آذار 2008 حتى نهاية حزيران 2009 وعمدنا في هذه الدراسة إلى تحليل واقع التنوع النباتي في منطقة العيسوية - اللاذقية وحصر الأنواع النباتية المنتشرة فيها والتعرف على بعض الجوانب المتعلقة بالنشاط البشري وتسليط الضوء على أهم الأخطار التي تهدد الحياة النباتية في هذه المنطقة. لقد أظهرت الدراسة تنوعاً في الغطاء النباتي كما أظهرت أنّ المنطقة تعرضت لمجموعة من العوامل مثل القطع غير المنظم والحرائق المتعاقبة، الأمر الذي أدى إلى تدهور الغابة وتغيير تركيبها النوعي مما يتطلب اتخاذ الإجراءات اللازمة لزيادة الوعي البيئي لدى السكان المحليين واقتراح خطة التنمية المستدامة للأنواع النباتية. This research was conducted in the period from the beginning of March 2008 to the end of June 2009. In this study, we attempted to analyzed the status of plant diversity in Al’Aysawiyya region - Lattakia, and identify the plant species prevailing there, recognizing some of the aspects related to human activity, and highlighting the most important risks which endanger the flora in this region. The study reveals diversity in the vegetation cover in the region. It also reveals that the region had undergone a series of factors, like disorganized logging, and successive fires, which led to the deterioration of the forest and changing its vegetation structure, which requires taking the necessary measures so as to increase ecological awareness among local population and propose the sustainable development plan for plant species.